2017
DOI: 10.1371/journal.pone.0180674
|View full text |Cite
|
Sign up to set email alerts
|

Improving numeracy through values affirmation enhances decision and STEM outcomes

Abstract: Greater numeracy has been correlated with better health and financial outcomes in past studies, but causal effects in adults are unknown. In a 9-week longitudinal study, undergraduate students, all taking a psychology statistics course, were randomly assigned to a control condition or a values-affirmation manipulation intended to improve numeracy. By the final week in the course, the numeracy intervention (statistics-course enrollment combined with values affirmation) enhanced objective numeracy, subjective nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
64
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 57 publications
(99 reference statements)
2
64
1
Order By: Relevance
“…Besides being theoretically important to social comparison scholars, these results counter to what was predicted are particularly relevant to decision-making researchers working on interventions for boosting numeracy as a way to educate good decisions (Peters et al, 2017). In our preliminary data and first experiment (see Data S1), the vast majority of students expressed interest in seeing a peer's work:…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Besides being theoretically important to social comparison scholars, these results counter to what was predicted are particularly relevant to decision-making researchers working on interventions for boosting numeracy as a way to educate good decisions (Peters et al, 2017). In our preliminary data and first experiment (see Data S1), the vast majority of students expressed interest in seeing a peer's work:…”
Section: Discussioncontrasting
confidence: 67%
“…Besides being theoretically important to social comparison scholars, these results counter to what was predicted are particularly relevant to decision‐making researchers working on interventions for boosting numeracy as a way to educate good decisions (Peters et al, ). In our preliminary data and first experiment (see Data S1), the vast majority of students expressed interest in seeing a peer's work: Teachers may be inclined to give students what they ask for; yet our research shows that exposing students to poor peer work is likely to decrease, rather than help, confidence in mathematical ability.…”
Section: Discussionmentioning
confidence: 68%
“…Responses in this artificial, carefully constructed, task highlight information processing differences between more and less numerate individuals. The results are interesting, in part, because, compared with the less numerate, the highly numerate generally make better decisions with numbers and experience better health and financial outcomes (Peters et al, ). In this task, however, the highly numerate make worse judgments.…”
Section: Discussionmentioning
confidence: 99%
“…Similar ideas related to boosting self-affirmations have been tested in supporting learning in statistics. Peters et al (2017) showed that through an affirmation-intervention during a statistics course they produced a positive influence on both students' subjective view of their ability as well as their actual ability.…”
Section: Discussionmentioning
confidence: 99%